An investigation into the effects of instructed extinction on physiological responding and conditional stimulus valence in human differential fear conditioning - Luck, Camilla Crystal (Curtin University, 2016)
The current thesis investigated the influence of instructed extinction on conditional stimulus (CS) valence and physiological responding in human differential fear conditioning. Instructed extinction reduced differential physiological responding, but did not affect CS valence evaluations. The results were not mediated by a general reduction in arousal levels and suggest that cognitive interventions targeting expectations of the unconditional stimulus occurring reduce heightened physiological responses but do not influence the subjective dislike of the feared stimulus.